(untitled) (مجلة ديالى للبحوث الانسانية, 2023)
This study is an attempt to review one of the increasing phenomena in English varieties around the world: L-vocalisation. It seeks to shed light on the nature of this phenomenon as well as the contexts in which it is possible. It also highlights the social behaviour of this feature and how it is spreading to different places where English is spoken. A historical overview of the genesis of this phenomenon is also given reviewing in the process the main studies that tracked its occurrence in different English varieties. The study thus captures some prominent observations reported on the behaviour of L-vocalisation. The study concludes that while this feature is well-established, there are potential lines of further research that can be pursued as regards L-vocalisation.